Klasifikasi Siswa Menggunakan Bayesian Classification Di Uptd Smp Negeri 2 Baron - Yenita Endah Puspitowati; Mumun Nurwilawati; Daniel Swanjaya (Informatics Engineering Department-UWKS, 2021)
To provide learning for students is not enough only in academics , but also needed in non- academic fields such as counseling . With counseling , psychological known how the students with what they are experiencing , so it takes the handling of student counseling . Giving questionnaire or questionnaires to students is a way to find out the problems in a natural student . This research is the development of the students' classification problems using Bayesian classification . Data obtained using a questionnaire that has been converted into a computerized , then weighted and processed using a Bayesian classification to obtain results in student services . Classification of students using Bayesian classification can generate services to students in accordance with the natural problems in students . Through the classification of students with Bayesian classification devote facilitate students in their personal problems without difficulty or feel embarrassed , but it also helps administrators in data processing to generate the appropriate student services on student issues . The use of Bayesian classification algorithm is suitable to assist performance and efficiency while counseling guidance teachers in performing services to students.